A Compact and Broadband Splitter to Interface Between Strip and Slot Waveguides - Devika Padmakumar Nair; Michael Menard (IEEE Photonics Journal)
We demonstrate a compact and low-loss 1 × 2 power splitter that efficiently splits and couples light from one strip to two slot waveguides. The splitter is optimized over a broad wavelength span ranging from 1.3 to 1.7 ${μ }$ m through finite difference time domain simulations. The splitter junction footprint is only 2.00 × 1.61 ${μ }$ m. The structure does not require an adiabatic transition region and is compatible with standard commercial silicon photonic fabrication processes. Experimental results show an insertion loss of less than 0.7dB for the TE polarization.